2018
DOI: 10.3390/coatings8100368
|View full text |Cite
|
Sign up to set email alerts
|

Development of Silane-Based Coatings with Zirconia Nanoparticles Combining Wetting, Tribological, and Aesthetical Properties

Abstract: Silane-based coatings with nanoparticles have been widely used in applications related to surface protection. Between them, the improvement of corrosion resistance by increasing the hydrophobicity is one of the main research goals. However, most coatings present problems of low wear resistance and poor aesthetic appearance. Therefore, the overall goal of this research is to manufacture hydrophobic sol-gel coatings based on silanes which comply with good tribological and aesthetical properties. In the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Authors use nanoparticles of different types to improve the wear performance of different resins, e.g. clay [1], ZrO2 [11], SiAlON [12], TiO2 [13], or even silica nanocontainers [14], with SiO2 nanoparticles being the ones most used [5,10,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Authors use nanoparticles of different types to improve the wear performance of different resins, e.g. clay [1], ZrO2 [11], SiAlON [12], TiO2 [13], or even silica nanocontainers [14], with SiO2 nanoparticles being the ones most used [5,10,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Composite zeolite-based coatings still require further development in order to meet the various application challenges induced by the industrial sector. Furthermore, in addition to the aforementioned characteristics of long durability, other new relevant requirements need to be considered, such as aesthetics, environmental sustainability, and hydrophobicity [122][123][124][125][126].…”
mentioning
confidence: 99%
“…Anyway, the Δ E is always less than 1.2, and there are studies that indicate that the color change is not important or appreciable if it does not exceed the value of 10 [ 61 ]. In any case, other authors have reported bigger changes in the Δ E of their coatings after nanoadditions [ 11 , 62 ].…”
Section: Resultsmentioning
confidence: 83%